Clinical and histopathological features of myofibrillar myopathy in Warmblood horses. (26th June 2017) - Valberg, S. J.; Nicholson, A. M.; Lewis, S. S.; Reardon, R. A.; Finno, C. J.
Summary: Background: To report a novel exertional myopathy, myofibrillar myopathy (MFM) in Warmblood (WB) horses. Objectives: To 1) describe the distinctive clinical and myopathic features of MFM in Warmblood horses and 2) investigate the potential inheritance of MFM in a Warmblood family. Study design: Retrospective selection of MFM cases and prospective evaluation of a Warmblood family. Methods: Retrospectively, muscle biopsies were selected from Warmblood horses diagnosed with MFM and clinical histories obtained (n = 10). Prospectively, muscle biopsies were obtained from controls (n = 8) and a three generation WB family (n = 11). Samples were assessed for histopathology [scored 0–3], fibre types, cytoskeletal and Z disc protein aggregates, electron microscopic alterations (EM) and muscle glycogen concentrations. Results: Myofibrillar myopathy‐affected cases experienced exercise intolerance, reluctance to go forward, stiffness and poorly localised lameness. Abnormal aggregates of the cytoskeletal protein desmin were found in up to 120 type 2a and a few type 2x myofibres of MFM cases. Desmin positive fibres did not stain for developmental myosin, α actinin or dystrophin. Scores for internalised myonuclei (score MFM 0.83 ± 0.67, controls 0.22 ± 0.45), anguloid atrophy (MFM 0.95 ± 0.55, controls 0.31 ± 0.37) and total myopathic scores (MFM 5.85 ± 2.10, controls 1.41 ± 2.17) were significantly higher in MFM cases vs. controls. Focal Z disc degeneration, myofibrillar disruption and accumulation of irregular granular material was evident in MFM cases. Muscle glycogen concentrations were similar between MFM cases and controls. In the Warmblood family, desmin positive aggregates were found in myofibres of the founding dam and in horses from two subsequent generations. Main limitations: Restricted sample size due to limited availability of well phenotyped cases. Conclusions: A distinctive and potentially heritable form of MFM exists in Warmblood horses that present with exercise intolerance and abnormal hindlimb gait. Muscle tissue is characterised by ectopic accumulation of desmin and Z disc and myofibrillar degeneration.